2019
DOI: 10.1111/1475-6773.13119
|View full text |Cite
|
Sign up to set email alerts
|

Good Samaritan harm reduction policy and drug overdose deaths

Abstract: Objective To examine the effects of a harm reduction policy, specifically Good Samaritan (GS) policy, on overdose deaths. Data Sources/Study Setting Secondary data from multiple cause of death, mortality records paired with state harm reduction and substance use prevention policy. Study Design We estimate fixed effects Poisson count models to model the effect of GS policy on overdose deaths for all, prescription, and illicit drugs, controlled substances, and opioids, while controlling for other harm reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…68 However, a morerecentstudyonGoodSamaritanlawsfoundnosignificanteffectonopioid-relatedoverdosemortality. 102 Similarly, studies on pill-mill laws that we reviewed found an increase in the number of opioid prescriptions in Texas 58,59 and opioid-related mortality in Florida 57 ; however, a 2019 study foundnulleffectsofpill-milllawsonopioidprescriptionsin Ohio and Tennessee, despite robust enforcement of these laws. 103 Two additional studies in 2019 on medical marijuana policies found lower rates of opioid use in areas with legalized medical marijuana policy than in areas without such policy, consistent with our results.…”
Section: Discussionmentioning
confidence: 89%
“…68 However, a morerecentstudyonGoodSamaritanlawsfoundnosignificanteffectonopioid-relatedoverdosemortality. 102 Similarly, studies on pill-mill laws that we reviewed found an increase in the number of opioid prescriptions in Texas 58,59 and opioid-related mortality in Florida 57 ; however, a 2019 study foundnulleffectsofpill-milllawsonopioidprescriptionsin Ohio and Tennessee, despite robust enforcement of these laws. 103 Two additional studies in 2019 on medical marijuana policies found lower rates of opioid use in areas with legalized medical marijuana policy than in areas without such policy, consistent with our results.…”
Section: Discussionmentioning
confidence: 89%
“…Seven studies examined NALs dichotomously, and only one [19] did not also account for specific NAL components. Six studies dealt with potential issues of multicollinearity by collapsing components or running individual models for each component.…”
Section: Resultsmentioning
confidence: 99%
“…However, three studies that extended the study time‐frame to 2015 or 2016, just as the most recent fentanyl outbreak was unfolding in parts of the country, reported a null effect overall for NALs and overdose deaths [12,18,19], and one found an increase in overdose deaths following NAL adoption [20]. Using data from 1999 to 2016, Atkins et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations